The Efforts of Sharjah Government in Enhancing the Community Awareness in Reviving and Protecting the Heritage of Sharjah Emarite - Alnaqabi, khawla; Jamhawi, Monther (Al-Adab Journal, 2025)
The study aims to review the role of the Emirates and the Sharjah administration in taking care of heritage, first by defining the meaning of heritage and clarifying the concept of heritage awareness, then by examining the efforts of the government in merging the heritage with education, media, and law, in addition to establishing various cultural activities, especially the Sharjah Heritage Institute and reviewing all its activities. In the theoretical chapters, the study shows the steps taken by Sharjah to enhance awareness of heritage among the population, while in the applied section of the study is measuring the awareness of heritage among the population, via an electronic questionnaires and analysis of it to find out the percentage of heritage awareness among the youth and the citizens in order to reach the results and recommendations of this study.